2023
DOI: 10.3389/fpubh.2023.1127745
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy and the willingness to recommend the COVID-19 vaccine to children in a rural country on the United States-Mexico border

Abstract: IntroductionAs of October 26, 2022, only 9% of children in the United States aged 6 months to 4 years have received at least one dose of COVID-19 vaccine despite FDA approval since June 17, 2022. Rates are better yet still low for children aged 5 to 11 years as nearly 30% were fully vaccinated as of August 23, 2022. Vaccine hesitancy among adults is one of the major factors affecting low vaccine uptake rates in children against COVID-19, yet most studies examining vaccine hesitancy have targeted school-age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Studies developed in other countries have also reported side effects from the COVID-19 vaccine as being the most common concern expressed regarding both children under 5 years and 5-12 years [11,12]. Another study evaluating COVID-19 vaccine uptake among healthcare workers in Albania observed that staff living in households with ≥4 members who were supposed to have dependent children in the house were less likely to receive a third COVID-19 vaccine dose compared with two-person households [13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies developed in other countries have also reported side effects from the COVID-19 vaccine as being the most common concern expressed regarding both children under 5 years and 5-12 years [11,12]. Another study evaluating COVID-19 vaccine uptake among healthcare workers in Albania observed that staff living in households with ≥4 members who were supposed to have dependent children in the house were less likely to receive a third COVID-19 vaccine dose compared with two-person households [13].…”
Section: Discussionmentioning
confidence: 99%